Simple procedure applying lactose induction and one‐step purification for high‐yield production of rhCIFN. (11th October 2015) - Bashir, Hamid; Ahmed, Nadeem; Khan, Mohsin Ahmad; Zafar, Ahmad Usman; Tahir, Saad; Khan, Muhammad Islam; Khan, Faidad; Husnain, Tayyab
Abstract: Recombinant consensus interferon (CIFN) is a therapeutic protein with molecular weight of 19.5 kDa having broad spectrum antiviral activity. Recombinant human CIFN (rhCIFN) has previously been expressed in Escherichia coli using isopropyl‐β‐d ‐thiogalactopyranoside (IPTG), a non‐metabolizable and expensive compound, as inducer. For economical and commercial‐scale recombinant protein production, it is greatly needed to increase the product yield in a limited time frame to reduce the processing cost. To reduce the cost of production of rhCIFN in E. coli, induction was accomplished by using lactose instead of IPTG. Lactose induction (14 g/L) in shake flask experiment resulted in higher yield as compared with 1 mM IPTG. Finally, with single‐step purification on DEAE sepharose, 150 mg/L of >98% pure rhCIFN was achieved. In the present study, an attempt was made to develop a low cost process for producing quality product with high purity. Methods devised may be helpful for pilot‐scale production of recombinant proteins at low cost.